Redirecting pantoprazole as a metallo-beta-lactamase inhibitor in carbapenem-resistant Klebsiella pneumoniae - Abdulaal, Wesam H.; Alhakamy, Nabil A.; Asseri, Amer H.; Radwan, Mohamed F.; Ibrahim, Tarek S.; Okbazghi, Solomon Z.; Abbas, Hisham A.; Mansour, Basem; Shoun, Aly A.; Hegazy, Wael A. H.; Abdel-Halim, Mahmoud Saad (Frontiers in Pharmacology, 2024)
The development of resistance to carbapenems in Klebsiella pneumoniae due to the production of metallo β-lactamases (MBL) is a critical public health problem because carbapenems are the last resort drugs for treating severe infections of extended-spectrum βlactamases producing Klebsiella pneumoniae. Restoring the activity of carbapenems by inhibition of metallo β-lactamases is a valuable approach to combat carbapenem resistance. In this study, two clinical well-characterized multidrug and carbapenem-resistant Klebsiella pneumoniae were used. Sub-inhibitory concentrations of pantoprazole and the well-reported metallo β-lactamase inhibitor captopril inhibited the hydrolytic activities of metallo β-lactamases with pantoprazole having more inhibiting activity. Both drugs, when used in combination with meropenem exerted synergistic activities. Pantoprazole could also downregulate the expression of the metallo β-lactamase genes blaNDM and blaVIM. Docking study revealed that pantoprazole could bind to and chelate zinc ions of New Delhi and VIM metallo β-lactamase enzymes with higher affinity than the control drug captopril and with comparable affinity to the natural ligand meropenem indicating the good inhibitory activity of pantoprazole against metallo β-lactamases.In conclusion, pantoprazole can be used in combination therapy with meropenem as a new strategy for treating serious infections caused by metallo-B-lactamses producing K. pneumoniae.